PENERAPAN PENTA HELIX MODEL PADA PENGELOLAAN CAGAR BUDAYA SITUS RADIO MALABAR OLEH DINAS BUDAYA DAN PARIWISATA KABUPATEN BANDUNG - Rukmana, Asep R.; Hakim, Rizal Abdul; Maryam, Neneng Siti (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
Research conducted at the Cultural Heritage Site of Malabar Radio Station Bandung Regency, this is in line with lifestyle changes, urbanization, and technological developments often pose threats to the sustainability of existing Cultural Heritage Sites. The purpose of this study is to analyze how the management collaboration between the Bandung Regency government and related stakeholders regarding the management of the cultural heritage site of Malabar radio station. The theoretical model used as the basis of this research is the helix model with a penta helix strategy in the management of cultural heritage sites, which involves an active role in the form of cooperation from the government, business/private sector academics, the community and the mass media. The method used in this study is a qualitative method with a descriptive type of research, with the data collection technique being through observation, interviews and documentation. The results of the study show that the management of the Malabar Radio Station Cultural Heritage Site has involved various parties with complementary roles. However, the main challenges lie in cross-sectoral coordination, policy consistency, and strengthening community institutions in the form of training, the formation of tourism-aware organizations, and long-term formal cooperation. Continuous collaboration between stakeholders is needed to make this site a model for the preservation and development of cultural heritage that is integrative, productive, and sustainable. The researcher suggested that the management of the Malabar Radio Site needs to be improved through cross-sectoral collaboration, community training, and sustainable preservation strategies. Improving facilities and digital promotion is also important to expand tourist attractions and visits.